Patriarchal nature of mourning from an African perspective - Khosa-Nkatini, Hundzukani P. (HTS teologiese studies, 2022)
It is common in African culture for a widow to wear black or navy clothes as a sign of mourning her husband upon his death. Widows in Africa are expected to mourn for a certain period. In South Africa, most African ethnic groups expect them to mourn for a period of 12 months. Vows in the western culture state ‘until death do us part’, but this is not the case in the African traditions. A widow is still considered married even after the death of her husband. She must undergo mourning rituals as a widow to mourn her husband. The article extensively analysed the general processes that African families undergo after the death of a family member. It is important to note that most African traditions surrounding death are stricter for women than for men. This is because women undergo many rituals before they are considered clean enough to re-marry. This is the opposite for men as they have a shorter mourning period with less rituals. In this regard, the mourning process in African countries is governed significantly by patriarchal ideologies.Contribution: The main aim of this article is to effectively analyse the mourning process in most African countries and how all the processes are evidently a by-product of the patriarchal nature of the societies.